Blocking Migration of Polymorphonuclear Myeloid-Derived Suppressor Cells Inhibits Mouse Melanoma Progression - Groth, Christopher (Cancers (Basel), 2021)
SIMPLE SUMMARY: Myeloid-derived suppressor cells (MDSC) represent a heterogeneous myeloid cell population that is expanded in tumor bearing hosts and substantially contributes to immunosuppression, representing thereby a valuable therapeutic target. Our study analyzes polymorphonuclear (PMN) and monocytic (M) MDSC subsets regarding their immunosuppressive capacity and recruitment mechanisms in murine melanoma. The immunosuppressive activity of both subsets was comparable. We identified the C-X-C Motif Chemokine Receptor (CXCR) 2/chemokine C-X-C motif ligand (CXCL) 1 axis as an important mediator of PMN-MDSC recruitment. Inhibition of CXCR2 resulted in a decreased infiltration of tumors with PMN-MDSC and increased survival of melanoma bearing mice. Furthermore, adjuvant treatment of mice with resected tumors reduced the infiltration of pre-metastatic sites with PMN-MDSC and the occurrence of distant metastasis. The decrease in PMN-MDSC infiltration was accompanied by an increase in natural killer (NK) cell frequency, suggesting an important role of PMN-MDSC in suppressing the NK cell-mediated anti-tumor response. ABSTRACT: Background: Despite recent improvement in the treatment of malignant melanoma by immune-checkpoint inhibitors, the disease can progress due to an immunosuppressive tumor microenvironment (TME) mainly represented by myeloid-derived suppressor cells (MDSC). However, the relative contribution of the polymorphonuclear (PMN) and monocytic (M) MDSC subsets to melanoma progression is not clear. Here, we compared both subsets regarding their immunosuppressive capacity and recruitment mechanisms. Furthermore, we inhibited PMN-MDSC migration in vivo to determine its effect on tumor progression. Methods: Using the RET transgenic melanoma mouse model, we investigated the immunosuppressive function of MDSC subsets and chemokine receptor expression on these cells. The effect of CXCR2 inhibition on PMN-MDSC migration and tumor progression was studied in RET transgenic mice and in C57BL/6 mice after surgical resection of primary melanomas. Results: Immunosuppressive capacity of intratumoral M- and PMN-MDSC was comparable in melanoma bearing mice. Anti-CXCR2 therapy prolonged survival of these mice and decreased the occurrence of distant metastasis. Furthermore, this therapy reduced the infiltration of melanoma lesions and pre-metastatic sites with PMN-MDSC that was associated with the accumulation of natural killer (NK) cells. Conclusions: We provide evidence for the tumor(−)promoting properties of PMN-MDSC as well as for the anti-tumor effects upon their targeting in melanoma bearing mice.